Sengketa Merek Dagang Geprek Bensu dalam Perspektif Hukum Hak Kekayaan Intelektual - Komang Cahyaniarsa Suryaningrat; Ni Komang Irma Adi Sukmaningsih (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Intellectual property rights (IPR) are an important legal tool for trademark ownership, protecting business quality, and protecting a company's economic interests. Consumers build trust in trademarks because they signal distinct product quality and reflect a positive and consistent corporate image. Trademark protection is regulated by national law under Trademark Law No. 20 of 2016, which provides legal certainty for trademark owners. This law stipulates that a trademark is only valid if it has distinctive elements, is not imitative, and has been officially registered with an authorized institution. The "first come, first served" principle in Indonesian trademark law can be interpreted as a mechanism that grants rights to the first party to file a valid application. However, the application of this principle in practice often raises complex legal issues, particularly when a trademark has already gained widespread public recognition prior to its formal registration. This study focuses on evaluating this legal protection through a normative legal research method by examining applicable laws, regulations, and court decisions related to trademark disputes in Indonesia. The Geprek Bensu dispute has attracted public attention because it highlights the conflict between legal provisions regarding trademark ownership and public perception. This case demonstrates that the existing legal framework still requires further refinement to balance the interests of trademark registrants with those of parties who have built public reputation through prior commercial use. Therefore, legal reform and consistent law enforcement are essential to ensure fair and comprehensive trademark protection in Indonesia.